Quantitative real-time PCR assay with immunohistochemical evaluation of HER2/neu oncogene in breast cancer patients and its correlation with clinicopathological findings - Nadia Gheni; David Westenberg (Wolters Kluwer Medknow Publications, 2020)
Human epidermal growth factor receptor HER2/neu status is an important prognostic factor for breast cancer as it is crucial in stimulating growth and cellular motility. Overexpression of HER2/neu is observed in 10%−35% of the human breast cancer and is associated with prognosis and response to treatment. The magnitude of amplification must be determined to facilitate better prognosis and personalized therapy in the affected patient. This study aims to investigate the HER2/neu status in breast cancer by concurrent HER2/neu protein overexpression immunohistochemically with HER2/neu DNA amplification by quantitative real-time polymerase chain reaction (PCR), allowing accurate and precise quantification of HER2/neu amplification after a follow-up period. A total of 54 paired tissue samples from formalin-fixed paraffin-embedded (FFPE) breast cancer patients enrolled in this study were collected to evaluate tumor and normal tissues. Only cases with 80% and more tumor cells were included. For confirmation of immunohistochemistry (IHC) results, qPCR was used to determine the HER2/neu amplification. The association between clinicopathological variables like age, tumor size, histological grade, stage, lymph node status, hormone receptor status, family history, recurrence rate, and vital status was evaluated. We observed that 11/54 (20.4%) of the tumor tissues are positive for HER2/neu protein overexpression by IHC. A total of 8 out of these 11 cases (72.7%), which presented a score of 3+, showed gene amplification of HER2/neu. The concordance rate between IHC and qPCR was 94.4%. HER2/neu gene amplification was found to be significantly associated with recurrence, increased risk of death, and progesterone receptor status, supporting a negative prognostic role of HER2/neu in breast cancer survival. In conclusion, IHC can be used as an initial screening test to detect HER2/neu protein overexpression, and the use of qPCR can verify the IHC results and establish HER2/neu status in routine clinical practice.